2020
DOI: 10.1038/s41598-020-70891-5
|View full text |Cite
|
Sign up to set email alerts
|

Emerging predictors of femoral artery occlusion after pediatric cardiac catheterization

Abstract: Long 3 , feng tang 2 & Lei Li 2* the objective was to review the prevalence of femoral artery occlusion (fAo) after cardiac catheterization in children up to 12 years old from two centers in China and identify its related risk factors. After collecting clinical data from patients who had undergone pediatric cardiac catheterization, univariate and multivariate analysis were used to evaluate the correlations between fAo and clinical factors, including sex, age, height, weight, sheath size, operation time, therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…A study by Tadphale et al suggested that a diameter of less than 3 millimeters in the femoral artery and a ratio of sheath outer diameter to vascular lumen diameter greater than 50% are associated with an increased risk of experiencing palpable disappearance of femoral artery pulsation at the end of surgery [26]. Multiple studies have shown that low body weight, larger arterial sheath diameter, and longer surgical time are independent risk factors for femoral artery injury [27]. Alexander et al indicated that the use of ultrasound guidance in pediatric cardiac catheterization can reduce the incidence of loss of arterial pulse (LOP) requiring treatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Tadphale et al suggested that a diameter of less than 3 millimeters in the femoral artery and a ratio of sheath outer diameter to vascular lumen diameter greater than 50% are associated with an increased risk of experiencing palpable disappearance of femoral artery pulsation at the end of surgery [26]. Multiple studies have shown that low body weight, larger arterial sheath diameter, and longer surgical time are independent risk factors for femoral artery injury [27]. Alexander et al indicated that the use of ultrasound guidance in pediatric cardiac catheterization can reduce the incidence of loss of arterial pulse (LOP) requiring treatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Known complications of trans-catheter occlusion of coronary artery fistulas include residual shunt due to incomplete closure, myocardial ischemia due to closure of side branches of peripheral normal coronary artery, coil migration and embolization in the right ventricular system, transient ST changes on electrocardiograms, and atrioventricular block [ 7 ]. In addition, there is a significant risk of complication at the site of arterial puncture in infants weighing less than 4 kg [ 11 ]. The risk of complication is high in the first 6 months of life, and 0.23% of deaths are reported in neonates [ 12 ].…”
Section: Discussionmentioning
confidence: 99%